EKSTRAKSI DNA DAN AMPLIFIKASI ITS rDNA ISOLAT FUNGI ENDOFIT LBKURCC67 UMBI TANAMAN DAHLIA (DAHLIA VARIABILIS) - Senjavi Rakhmana; Saryono '; Titania Tjandrawati Nugroho (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
> Endophyte fungi lives in the plant tissues without causing harm to their host and has known that can produce secondary metabolite and extracellular enzyme. Fungi LBKURCC67 is an endophyte fungi that was isolated from tubers of yellow flowered Dahlia variabilis in Padang Panjang, West Sumatera. Species of fungi LBKURCC67 isolate was not known exactly because the morphology identification has been previously is appropriate for genus level. The accurate identification to known species is molecular with phylogenetic analysis. Before determine species in molecular analysis, it must extraction and amplification DNA. This research aims to optimation of DNA extraction and rDNA amplification in Internal Transcribed Spacer (ITS) regions with Polymerase Chain Reactions (PCR) methods. The DNA of fungi LBKURCC67 isolate was extract with Wizard Genomic DNA Purification kit ex Promega Corp. (Madison, USA) from cultur mycelium. The result shows extraction DNA was success from fourth days mycelia. Optimum condition for rDNA amplification with PCR were used ITS5 and ITS4 primers and 41°C annealing temperature. Electrophoresis analysis shows molecular weight of DNA isolate is 16.951 bp and molecular weight of PCR product is 583 bp.